Favorable outcome of Epstein-Barr virus-associated B-cell lymphoproliferative disorder complicated by immunoglobulin G4-related disease treated with rituximab-based therapy: a case report. (December 2016) - Ueda, Koki; Ikeda, Kazuhiko; Ogawa, Kazuei; Sukegawa, Masumi; Sano, Takahiro; Kimura, Satoshi; Suzuki, Osamu; Hashimoto, Yuko; Takeishi, Yasuchika
Abstract Background After acute infection of Epstein-Barr virus, Epstein-Barr virus-infected B cells survive but usually do not show clonal proliferation. However, Epstein-Barr virus-infected B cells occasionally acquire a proliferative capacity that provokes clonal lymphoproliferative disorders. We herein present a case with Epstein-Barr virus-infected CD30+ B cell and immunoglobulin G4+ plasmacytoid cell proliferation in the lymph nodes, suggesting a pathological and clinical interaction between Epstein-Barr virus-associated B-cell lymphoproliferative disorders and immunoglobulin G4-related disease. Immunoglobulin G4-related disease has been recognized as a benign disease with proliferation of IgG4-related disease+ plasmacytoid cells. Several studies have recently reported the coexistence of immunoglobulin G4-related disease+ plasmacytoid cells with Epstein-Barr virus-infected B cells in lymph nodes in some immunoglobulin G4-related disease cases. However, the pathogenic role of the clonal proliferation of Epstein-Barr virus-infected B cells in immunoglobulin G4-related disease, as well as the treatments for patients with both Epstein-Barr virus-infected B cells and immunoglobulin G4-related disease, have never been discussed. Case Presentation A 50-year-old Japanese man was referred to us for persistent fatigue and lymphadenopathy. His blood examination showed elevated IgG4, and detected high levels of Epstein-Barr virus DNA. A lymph node biopsy revealed IgG4+ plasmacytoid cells and infiltration of large lymphoid cells, which were positive for CD20, CD30, Epstein-Barr virus-related late membrane protein 1, and Epstein-Barr virus-encoded RNA, and were negative for IgG4. Based on the diagnosis of both Epstein-Barr virus-associated B-cell lymphoproliferative disorder and IgG4-related disease, the patient received eight cycles of rituximab combined with cyclophosphamide and prednisolone, which resulted in the complete disappearance of lymphadenopathy. Moreover, his serum IgG4 level was significantly reduced, and plasma Epstein-Barr virus DNA became undetectable. Although prednisolone was transiently administered in each cycle of immunochemotherapy, the therapeutic effect has persisted for Epstein-Barr virus-associated B-cell lymphoproliferative disorder and IgG4-related disease as of 1 year after finishing treatment. Conclusions In the present case, clinical presentation and pathological findings revealed that Epstein-Barr virus-associated B-cell lymphoproliferative disorder coexisted with IgG4-related disease. Although several studies have described the relationship between Epstein-Barr virus-infected B cells and IgG4-related disease, this is the first report of a patient whose plasma Epstein-Barr virus DNA level, which correlated with the disease statuses of both diseases, was monitored. Moreover, rituximab-based immunochemotherapy was highly effective for both diseases. Our findings are suggestive for establishing a novel treatment strategy for IgG4-related disorders associated with chronic Epstein-Barr virus infection.